Differentiated effects of parasitic nematodes Phasmarhabditis hermaphrodita on slugs of the genus Deroceras and snails of the genus Arion - Pavlína Šenoldová; Jiří Rotrekl (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2005)
This paper compares efficiency of preparations based on a parasitic nematode species Phasmarhabditis hermaphrodita with a molluscocide containing methiocarb as an effective substance. Parasitic nematodes by the family Agriolimacidae showed a significantly better effect on mortality and reduction of the percentage of damaged plants than the methiocarb-based preparation. Under laboratory and field conditions, the efficiency of parasitic nematodes on the family Agriolimacidae ranged from 84% to 94% and from 81% to 94%, resp., while the percentages of damaged plants were minimal in both cases. The corresponding effects of the methiocarb-based molluscocide were only 35% and 21%, resp. The effect of parasitic P. hermaphrodita nematodes on members of the snail family Arionidae was not demonstrated both under laboratory and field conditons and the mortality was up to 6% with a total defoliation of plants. Under laboratory and field conditions, the mortality of slugs from the genus Arion after the application of methiocarb-based preparation was 53% and 38%, resp. However, the damage of plants was significant and it reached nearly 67% and 60% under laboratory and field conditions, resp.